The Effect of Village Budget Management and Utilization on Infrastructure Development: The Mediating Role of Community Participation in Simpang Rantau Gedang Village - Trirahmadi, Sugeng; Tan, Syamsurijal; Syuhada, Siti (Jurnal Sains Sosio Humaniora, 2026)
Village infrastructure development plays an important role in improving community welfare and supporting sustainable rural development. The success of infrastructure development is strongly influenced by the management and utilization of the Village Revenue and Expenditure Budget (APBDes) as well as the level of community participation. This study aims to analyze the direct and indirect effects of APBDes management and utilization on infrastructure development through community participation in Simpang Rantau Gedang Village, Mersam District. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to village residents and analyzed using path analysis with the assistance of SPSS software. The results indicate that APBDes management and utilization have a positive effect on community participation. Community participation has a significant effect on infrastructure development and serves as a mediating variable. The study concludes that transparent, accountable, and effective APBDes management, supported by active community participation, is essential for achieving equitable and sustainable village infrastructure development.